Description of a randomised controlled trial of inhaled corticosteroid/fast-onset LABA reliever therapy in mild asthma. Issue 3 (4th February 2016) - Beasley, Richard; Pavord, Ian; Papi, Alberto; Reddel, Helen K.; Harrison, Tim; Marks, Guy B.; Hancox, Robert J.; Weatherall, Mark
This paper describes the rationale and design of the Novel START (Symbicort Turbuhaler Asthma Reliever Therapy) randomised controlled trial of inhaled corticosteroid (ICS)/fast-onset long-acting β-agonist (LABA) reliever therapy in mild asthma. Description of a real world study of the novel ICS/fast-onset LABA reliever therapy regimen in mild asthma http://ow.ly/WE3Yp